Pengalaman Pasien Gangguan Jiwa Selama MengalamiRestrain Extremitas di Rumah Sakit Jiwa Arif Zainudin Surakarta - Saputra, Dwi, Arum Pratiwi, S.Kp., M.Kes (2017)
Violent behavior was a major problem that often occurs in patients with mental disorders. The impact of the violent behavior of mental patients in hospitals are at risk for the safety of patients, nurses and the surrounding environment. One way of handling mental patients who experienced violent behavior was restrain extremities. Action restrain extremities in the implementation of the poor can cause side effects in patients with both injury and physiological as well as psychological. This study aims to determine the patient experiences a mental disorder during their extremities restrain Mental Hospital in Surakarta. This study was a qualitative research with phenomenological approach. The study population was all mental patients who have experienced restrain RSJD in Surakarta. There were 5 patients with purposive sampling technique. Data collection research using interviews and data analysis using descriptive test. The study concluded that (1) the background does restrain the patient suffered violent behavior, (2) a feeling of patients undergoing restrain patients feel impaired physical body unwell, aches and swollen due to the limitations of motion experienced by patients during restrain and (3) the effects experienced by patients after the onset of exercise restrain the sores and blisters on the patient's body, as well as the feeling of being treated rudely by nurses causing a disturbance therapeutic nurse communication with patients.